(Re)Making a Difference Journal for Religion, Film and Media - Mia Lövheim (Journal for Religion, Film and Media, 2015)
This article presents and discusses how mediatisation as a theory can be used to analyse two commercial videos, one promoting the organisation Catholics Come Home and the other Coca Cola. A core question in the current debate on mediatisation and religion concerns if and how mediatisation changes not only the social forms of communication about religion but also the meaning of religion in society. The issue in focus for the analysis is whether these videos mirror attributes and roles traditionally associated with men and women within religious institutions or offer an alternative to these. By using gender as a lens, we can see that mediatisation challenges religious institutions to adapt their narratives and symbols to commercial media culture, but that also within this new setting some traditional female gender norms seem to remain or even become reinforced.